Tinjauan Al-Qur’an dan Hadits Sahih Terhadap Pemilihan Umum di Indonesia - Kurniawansyah, Khairul; Hermawan, Iwan; Waluyo, Kasja Eki (Lembaga Intelektual Muda (LIM) Maluku, 2024)
General elections are a system of election of leaders held in Indonesia every 5 years. In addition, Indonesia is the country with the most Muslim majority in the world. This has led scholars to argue whether elections should be held, and how the Qur'an and Hadith review are valid about elections. The method used in this research is a literature study with a qualitative approach. While the data collection technique used by researchers is a literature method by looking for data and information from various sources such as books, journals, and articles. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results revealed that there was no specific argument explaining elections, whereas during the caliph time it used deliberative means or was appointed by previous leaders. The argument contained in the Qur'an and hadith is how to criterion a good leader in Islam. Indonesian clerics argue that elections are permissible in Indonesia and not forbidden because they reduce harm and Muslims can elect leaders who are considered the least harmful.